Evaluation of different storage structures and monitoring of storage molds in onion genotypes for managing postharvest diseases - KRISHNAPRASAD; VEEREGOWDA, M.K. NAIK*, K. RAJU, G.S. DEVIKA RANI, (Indian Phytopathology, 2008)
Different onion storage structures were evaluated for black and blue mold occurrence in onion. Among them bottom ventilated single row storage structure with thatched roof was the best one for small farmers due to low severity (15-25%) of onion molds and low cost of construction. The modified bottom ventilated double row storage structure with asbestos roof was the best one for big farmers and traders because of high capacity with low spoilage. Ten onion genotypes when evaluated under storage condition by artificial inoculation using pin-prink method and monitored for mold infection upto 90 days after storage (DAS) the genotypes, Arka Kalyan and Arka Pitamber showed less severity (<10%) of black mold (Aspergillus niger) till 30 DAS and reached 20% severity by 45 DAS, thereafter increased steadily to reach up to 35-40% by 90 DAS. With regards to blue mold (Penicillium digitatum), Arka Kalyan remained absolutely free from infection up to 15 DAS, and showed less than 10 percent severity by 60 DAS and reached up to 20 percent severity by 90 DAS. Similarly, Arka Pitambar could also show 10 percent severity up to 45 DAS and withstood the blue mold severity up to 20 % by 75 DAS.